STRATEGI PEMBELAJARAN ABAD 21 - Maria Febrina Sianturi; Christina Natalia Simarmata; Serefine Aimelia Damai H; Susilo Bambang Jordan Situmorang; Syahrial Syahrial (JURNAL ILMIAH NUSANTARA, 2025)
21st Century Learning is a concept of an educational approach as a design to overcome the demands of the sophisticated and modern era where changes are increasingly complex and rapid. Competence in the 21st era is an important competency that must be possessed by students in order to be able to be involved in life clearly in the 21st Era. The purpose of this research is to determine what strategies to face the challenges of the 21st century learning system. This writing method uses literature reviews from several sources, such as journals, the internet, and books. The results of the study show that there are several strategies to deal with the challenges of the 21st century: Providing training and professional development to educators to update their knowledge and skills in teaching, managing classrooms, and using technology to increase learning effectiveness. This encourages educators to be better prepared to face the challenges of 21st century learning. The learning system in the 21st century is still a reason for more adequate education management, considering that there are challenges in the learning process for educators and students.